Teachers Views On Error Correction In Writing - Angrum, Alna Triskaya; Hasanah, Nur Izatil; Klaudiya, Dhei (Program Studi Pendidikan Bahasa Inggris, Universitas Pendidikan Muhammadiyah Sorong, 2020)
This study focuses on the qualitative study of Error Correction in writing provided by teachers who teach in urban and rural areas especially in Junior High School. Thus, the present study aims to investigate English teachers’ views of error correction in their writing classes, reasons and types of errors that they correct and their error correction strategies. The samples in this study are two teachers who teach in urban Junior High School and rural Junior High School. The data collection instrument is semi-structure interview. The results showed that EFL teachers believe that learners’ error should be corrected. They also believe that when students doing writing practice, teachers have to give feedback, or correction. The purpose of the correction is to make the students aware of their writing mistakes and how to correct them; thus, they would not make the same mistakes in the future. There are not differences between the learners in the urban and rural areas. The study concludes that teachers focus on repetitious errors made by learners. The teachers believe that they should concentrate on the errors that directly distort meaning, even though it’s only a typo; the teacher also should correct the students’ tasks.